Experimenting with academic subjectivity: collective writing, peer production and collective intelligence. Issue 1 (1st January 2019) - Peters, Michael A.; Besley, Tina; Arndt, Sonja
ABSTRACT: Following involvement in several academic collectively written articles, the authors question traditional notions of the 'lone' individualist author model as the expected standard in the humanities as opposed to large research teams in physical sciences. They use Barthes and Foucault to question the function and the concept of the author and assumed notions of subjectivity. Recent collective writing as a form of peer production and publishing is an attempt to reinvent the concepts of authorship, the author subject and author subjectivity. These bring to the fore the processes of peer review, questions of ownership (for example, of what remains in a revision, whose contribution becomes revised and by whom), and blurr the boundaries around author/collective voice and are discussed in this paper. Its transversality is proving as complex as the term suggests, in terms of developing new ways of connecting, thinking, examining and working, in ways that have not been the norm at least in the field of philosophy of education. Contemporary questions of the potential social, philosophical, legal, epistemological and ethical implications for and of authorship and subjectivity have barely been touched on to date, but this article begins to broach this gap.